2021
DOI: 10.1186/s12959-021-00330-6
|View full text |Cite
|
Sign up to set email alerts
|

COVID19 infection in a patient undergoing treatment for Paroxysmal Nocturnal Hemoglobinuria (PNH) with Ravulizumab

Abstract: Background In the recent COVID19 pandemic, patients with hematological disorders were considered at high risk for severe disease. Limited data is available regarding the course of COVID19 infection in this subgroup. Case Presentation We describe a case of a 32-year-old man with paroxysmal nocturnal hemoglobinuria (PNH) undergoing treatment with ravulizumab (Ultomiris) who presented with COVID19 infection. He experienced only mild symptoms and had a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…However, recently published data indicate that patients with PNH may only present with mild symptoms of COVID-19 despite or even because of eculizumab treatment [ 78 81 ]. Further studies are needed to validate these observations [ 78 81 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recently published data indicate that patients with PNH may only present with mild symptoms of COVID-19 despite or even because of eculizumab treatment [ 78 81 ]. Further studies are needed to validate these observations [ 78 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thromboprophylaxis in the context of C5 inhibition should be considered in patients with PNH and severe COVID-19 symptoms requiring hospitalization [78][79][80][81]. Note that patients with PNH and a history of thrombosis or other thrombophilic markers should receive secondary thromboprophylaxis while on C5 inhibition therapy, regardless of whether or not they have COVID-19.…”
Section: Other Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately, 35% of patients die within 5 years if untreated due to thrombosis and related complications. [10,11] The complement system activation is a critical component in the sequalae of COVID19 infection. Evidence suggests that severe outcomes in COVID19 infection are attributed to the excessive activation of the complement cascade leading to acute lung injury and associated is with an increased prothrombotic state.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a phase 3 clinical trial is ongoing (NCT04570397). Ravulizumab has been shown to reduce complement-mediated inflammatory damage associated with COVID-19 infection in patients with paroxysmal nocturnal hemoglobinuria (PNH), according to a clinical case report study [123] . Annane et al suggested that Eculizumab leads to improved survival and reduced hypoxia in patients with severe COVID-19 [124] .…”
Section: Ravulizumab and Eculizumabmentioning
confidence: 99%